2019
DOI: 10.1007/s11119-019-09693-3
|View full text |Cite
|
Sign up to set email alerts
|

Predicting plant available phosphorus using infrared spectroscopy with consideration for future mobile sensing applications in precision farming

Abstract: Phosphorus (P) fertilisation recommendations rely primarily on soil content of plant available P (P avl) that vary spatially within farm fields. Spatially optimized P fertilisation for precision farming requires reliable, rapid and non-invasive P avl determination. This laboratory study aimed to test and to compare visible-near infrared (Vis-NIR) and mid-infrared (MIR) spectroscopy for P avl prediction with emphasis on future application in precision agriculture. After calibration with the conventional calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 45 publications
(70 reference statements)
2
22
0
Order By: Relevance
“…Additionally, the RPD in our study (2.2) fits within the range of values obtained in these works (between 1.8 and 2.7). It is widely referred to in the literature that P can be indirectly detected by NIR spectroscopy if organically bound [34][35][36], which we believe is the reason for P detection in these soils. According to Morón and Cozzolino [35], the success of NIR spectroscopy in the calibration of P fractions in the soil is dependent on the selected reference method.…”
Section: Discussionmentioning
confidence: 69%
“…Additionally, the RPD in our study (2.2) fits within the range of values obtained in these works (between 1.8 and 2.7). It is widely referred to in the literature that P can be indirectly detected by NIR spectroscopy if organically bound [34][35][36], which we believe is the reason for P detection in these soils. According to Morón and Cozzolino [35], the success of NIR spectroscopy in the calibration of P fractions in the soil is dependent on the selected reference method.…”
Section: Discussionmentioning
confidence: 69%
“…The regions between 400–600 nm and 2300–2500 nm were repeatedly selected for all the different P pools by this method ( Figure 4 b, Table S2 ). In a recent study, the most relevant variables for P models were selected based on the variable importance in the projection (VIP) method and the PLSR coefficients, similar to our study, were located around 500 and 2200–2400 nm [ 51 ]. Another study in the same year identified important Pox regions at 454–660 nm and 1732–2312 nm based on five runs of the variable selection method Generic Algorithm (GA) followed by PLSR [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the few existing studies on macro nutrient prediction using portable (V)NIR/MIR spectroscopy show limited success (Wenjun et al 2014 ; Ji et al 2016a ). Poor prediction performance is commonly attributed to the absence of distinct features in the IR spectrum and varying relationships between total and available element content (Kuang et al 2012 ; Pätzoldt et al 2019 ). Consequently, the prediction models for available major and trace nutrients from soil spectra often prove to be less robust than those developed for particle size fractions and soil organic carbon.…”
Section: Discussionmentioning
confidence: 99%